Prevalence of preoperative asymptomatic deep vein thrombosis in patients undergoing elective general surgery for benign disease - Ken Hagiwara; Yutaka Watanabe; Takeki Suzuki; Yukiyasu Okamura; Hiroharu Yamashita (Annals of Gastroenterological Surgery, 2023)
Abstract Background The systemic inflammatory response following surgery as well as that of malignant disease itself is associated with a hypercoagulable state, and thromboprophylaxis is thus recommended during postoperative management of cancer patients. However, limited information is available on the prevalence of preoperative deep vein thrombosis (DVT) and its risk factors in surgical candidates, especially those receiving operations for benign diseases. Methods This is a retrospective observational study with data of all patients scheduled for elective general surgery between January 2011 and September 2020, undergoing lower extremity venous ultrasonography as preoperative screening for DVT. The prevalence of preoperative asymptomatic DVT was estimated and its associations with clinical variables were evaluated. Results Among 1512 patients included in the study, 161 (10.6%) had asymptomatic DVT before surgery. DVT prevalence was 13.7% in patients with malignant disease, while it was 8.6% in those with benign disease. The site of the thrombus was distal type in 141 (87.6%) patients, most commonly in the soleal vein. Advanced age (>70 years), female sex, and decreased hemoglobin level were significantly associated with preoperative asymptomatic DVT by multivariate analysis. The odds ratio for advanced age was the highest and rose as age increased. Malignant disease was not an independent risk factor for preoperative DVT. Conclusion This study showed the prevalence of asymptomatic DVT to be equal in patients with and without malignant disease undergoing elective general surgery. Preoperative DVT assessment is necessary regardless of the disease indicated for surgery, especially in patients with the risk factors identified in this study.